ANALISIS PERUMUSAN STRATEGI PADA PAWON MAEMI - Rahmatina, Dita Pradela; Kurniawati, Desi Tri (Jurnal Kewirausahaan dan Inovasi, 2023)
Competition between micro, small, and medium-sized enterprises (MSME) in Indonesia is increasing in every year. In order to survive, companies need to apply strategies that match their characteristics and environment. The objective of this research is to analyze the internal and external environments of Pawon Maemi and to determine the most suitable strategy to be applied by this catering business. This qualitative research uses primary data form interviews and observations and secondary data from books, journals, and websites. Following the analyses using IFE Matrix, EFE Matrix, SWOT Matrix, and QSPM, this study finds that the most appropriate strategy for the business is market penetration, as suggested by its TAS of 5.25.